Penerapan Model Pembelajaran Two Stay Two Stray Terhadap Hasil Belajar PPKn materi Globalisasi Siswa Sekolah Dasar - Bomantara Bomantara; Safrul Safrul (PIONIR: JURNAL PENDIDIKAN, 2022)
This study aims to determine whether there is an effect of problem solving learning model on the ability of Indonesian story questions for elementary school students. By using quantitative methods and quasi-experimental models with the type of post-test only control design. To see the extent to which this research has an effect on the ability of story questions, the researchers collected data through a post-test conducted by students. The results of this study indicate that the problem solving learning model has an effect on the ability of Indonesian language story questions for elementary school students as evidenced by statistical data for hypothesis testing using the t test with the results of the T_count> T_table with a score of 5.320> 2.002 so that this research can be said to have a significant influence on the ability Indonesian story questions for elementary school students. With these results, it can be said that the problem solving learning model is able to improve the ability of story questions, so that it can be used as a learning model used in the classroom.